2012
DOI: 10.1111/j.2042-7158.2012.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of efflux transport of the PDE5 inhibitors, vardenafil and sildenafil

Abstract: The involvement of P-gp, BCRP and MRP2 for vardenafil and the involvement of P-gp and BCRP for sildenafil in the secretory transport with linear absorptive transport may contribute to the limited intestinal absorption of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…1, 2). Because it has been reported that sildenafil is a substrate for P-gp, 8) it was used as a positive control in the present study. In LLC-PK 1 cells, the transport of sildenafil and tadalafil in both directions was increased periodically over 120 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1, 2). Because it has been reported that sildenafil is a substrate for P-gp, 8) it was used as a positive control in the present study. In LLC-PK 1 cells, the transport of sildenafil and tadalafil in both directions was increased periodically over 120 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Choi and Song 8) demonstrated that efflux transporters were involved in the mechanisms for the transcellular transport of sildenafil across Caco-2 cell monolayers. That is, the B to A transport of sildenafil was 8.81-fold greater than the A to B transport, suggesting limited intestinal absorption due to the efflux transporter-mediated secretion of sildenafil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations